The malaise in the civilization of Sigmund Freud: an ontological analysis from the labor category (Research, Society and Development, 2022)
What is the origin of psychic sufferings revealed with intensity in capitalist sociability? From this question, the general objective of this article was formulated: to understand the genesis of psychic sufferings in capitalist sociability and specific objectives: 1) to demonstrate the psychic sufferings from the work "the malaise in civilization" of Freud; 2) relate the psychic sufferings with the category "strange work" developed by Marx and present the associated work as a way to overcome the malaise of society. As a methodological procedure, the investigation of the object was carried out based on a qualitative research of the bibliographic type. For its development, the theoretical contributions of Freud (1996), Marx (2004), among others, were used. The results of the research were: psychic sufferings are the fruit of the development of the dialectical relationship between objectivity and subjectivity and the overcoming of these sufferings can only occur through a free and associated sociability.